Impact assessments of gender transformative interventions in Tanzania: Pre-analysis plan - Cole, Steve; Ferguson, Nathaniel; Heckert, Jessica; Hidrobo, Melissa; Mwakanyamale, Devis; Nwagboso, Chibuzo (International Food Policy Research Institute, 2025)
Transforming gender norms improves women’s wellbeing and may help close the agricultural productivity gap, yet evidence on pairing them with agriculture interventions is limited. We will test an innovative approach to developing and delivering gender transformative interventions with cassava producers in Tanzania. Using a cluster-randomized controlled trial, we examine the impact of these gender transformative interventions paired with standard agricultural service, compared to agricultural services alone, on the primary (gender norms, decision making, and women’s leadership) and secondary (agricultural productivity, women’s savings, and women’s access to land) outcomes. Qualitative methods will examine changes in intra-couple dynamics (communication, decision making, and division of labor).